Large Stimulation of Recalcitrant Dissolved Organic Carbon Degradation by Increasing Ocean Temperatures - Lønborg, Christian; Álvarez–Salgado, Xosé A.; Letscher, Robert T.; Hansell, Dennis A. (Frontiers in Marine Science, 2018)
More than 96% of organic carbon in the ocean is in the dissolved form, most of it with lifetimes of decades to millennia. Yet, we know very little about the temperature sensitivity of dissolved organic carbon (DOC) degradation in a warming ocean. Combining independent estimates from laboratory experiments, oceanographic cruises and a global ocean DOC cycling model, we assess the relationship between DOC decay constants and seawater temperatures. Our results show that the apparent activation energy of DOC decay (Ea) increases by 3-fold from the labile (lifetime of days) and semi-labile (lifetime of months) to the semi-refractory (lifetime of decades) DOC pools, with only minor differences between the world’s largest ocean basins. This translates into increasing temperature coefficients (Q10) from 1.7–1.8 to 4–8, showing that the generalised assumption of a constant Q10 of 2 for biological rates is not universally applicable for the microbial degradation of DOC in the ocean. Therefore, rising ocean temperatures will preferentially impact the microbial degradation of the more recalcitrant and larger of the three studied pools. Assuming a uniform 1ºC warming scenario throughout the ocean, our model predicts a global decrease of the DOC reservoir by 7 ± 1 Pg C. This represents a 15% reduction of the semi-labile + semi-refractory DOC pools.